Turn On Light Raspberry Pi To Reduce Traffic Jam - Ageng Setiani Rafika; Hendra Kusumah; Mayang Septiawati (Universitas Raharja, 2022)
Nowadays human and computer communication has changed from time to time. The change is aimed at making communication between humans and computers more efficient. Human needs for information and communication are increasing with digital communication, the microcontroller used is Raspberry Pi 3. The traffic conditions are very congested, using a manual system does not work optimally due to the number of undisciplined road users and the increasing amount of volume vehicles every year. Therefore it is very necessary that the LEDs are turned on to reduce the volume density of the vehicle, especially at the intersection, and can control the time of the traffic lights in accordance with the specified time. Internet of Things (IoT) uses Raspberry Pi 3, ESP8266 Wi-fi Module, Sensor RCWL 0516 and Blynk. Raspberry Pi 3 as the main controller uses wireless networks, and makes devices able to communication such as sending and receiving data. The Blynk application is able to provide information in real time as well as remote control monitoring. When the sensor detects, the ESP8266 Wi-fi Module will send traffic density notifications via Smartphone so that it can provide information on road conditions periodically. The purpose of this study is to monitor the condition of the road from a distance so that road users are disciplined in driving and do not commit violations when the red light is on.